2021
DOI: 10.7150/ijbs.59965
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists (GLP-1RAs): cardiovascular actions and therapeutic potential

Abstract: Type 2 diabetes mellitus (T2DM) is closely associated with cardiovascular diseases (CVD), including atherosclerosis, hypertension and heart failure. Some anti-diabetic medications are linked with an increased risk of weight gain or hypoglycemia which may reduce the efficacy of the intended anti-hyperglycemic effects of these therapies. The recently developed receptor agonists for glucagon-like peptide-1 (GLP-1RAs), stimulate insulin secretion and reduce glycated hemoglobin levels without having side effects su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 192 publications
2
77
0
Order By: Relevance
“…A number of studies has found that semaglutide and liraglutide could reduce the levels of blood lipids and blood pressure (BP), hence contributing to the reduction of atherosclerosis and CVDs (117)(118)(119). Moreover, GLP-1RAs were reported to inhibit the development of AS in animal models.…”
Section: Effects On Atherosclerosismentioning
confidence: 99%
“…A number of studies has found that semaglutide and liraglutide could reduce the levels of blood lipids and blood pressure (BP), hence contributing to the reduction of atherosclerosis and CVDs (117)(118)(119). Moreover, GLP-1RAs were reported to inhibit the development of AS in animal models.…”
Section: Effects On Atherosclerosismentioning
confidence: 99%
“…The functional and therapeutic difference in these two designations are exemplified by the actions of newer anti-diabetes drugs—these drugs including sodium-glucose transport protein 2 (SGLT2) inhibitors and glucagon-like peptide-1 (GLP-1) agonists have beneficial effects in large clinical trials where cardiovascular events and deaths are reduced by treatment with the index agents. It has however been very difficult to show consistent favorable actions on endothelial function assessed as enhanced vasodilation [ 25 , 26 ]. This suggests that the favorable cardiovascular effects arise from anti-inflammatory actions on the endothelium; these anti-inflammatory actions are more disparate and difficult to characterize than measures of vasodilatory capacity.…”
Section: Endothelial Dysfunction and Cardiovascular Diseasementioning
confidence: 99%
“…Therefore, this evidences the protective effects played by incretins on the atherosclerotic plaque for patients with acute coronary syndrome, in the condition of acute coronary thrombosis 38 and multivessel disease with and ED 39 . For a detailed review of cardiovascular actions and molecular targets of glucagon-like peptide-1 receptor agonists (GLP-1RAs) 36 and sodium glucose cotransporter 2 inhibitors (SGLT2i) 37 , please refer to our recent reviews. As mentioned above, ED can be an independent predictor of cardiovascular events and the first step toward coronary arteriosclerosis 40 .…”
Section: Diabetes and Cardiovascular Disease - The Dangerous Liaisonmentioning
confidence: 99%
“…As for the efficacy of SGLT2i 37 and GLP-1RAs 36 , numerous clinical studies have shown that metformin can improve vascular endothelial function and reduce CVD in patients with diabetes (see Table 1 152 - 167 ). A study reported in 2001, utilizing a moderate dose of metformin (500 mg twice daily) administered for 12 weeks and compared to placebo, showed improvement in Ach-stimulated flow (and IR) was observed among diet-treated T2D patients.…”
Section: Current Status Of Metformin In the Amelioration Of Edmentioning
confidence: 99%